A De Novo sSMC (22) Characterized by High-Resolution Chromosome Microarray Analysis in a Chinese Boy with Cat-Eye Syndrome. (28th February 2021) - Li, Jinjie; Zhang, Yue; Diao, Yanjun; Li, Rui; Jiang, Liqing; Zhou, Lei; Liu, Jiayun; Duan, Weixun; Yang, Liu
Abstract : We report a 15-year-old boy with cat-eye syndrome (CES) without short stature or intellectual disorder. The boy was confirmed by cytogenetic and high-resolution chromosome microarray analysis (CMA). The G-banding karyotype confirmed the de novo of the patient. Also, the CMA result showed 1.76 Mb tetrasomy of proximal 22Q11.1 ⟶ 22Q11.21 consistent with CES {arr22q11.1q11.21 (16, 888, 899–18, 644, 241) X4}, a typical small type I CES chromosome. The patient has many of the basic characteristics of CES; however, he is taller than his peers instead of shorter. It is rarely reported in the past since short stature is a common feature of this syndrome. Furthermore, the boy has no intellectual disorder and attends a normal school since he was six-year-old. What bothered him most were recurrent respiratory infections, retromicrognathia, and heart defects.